Glutamate receptors within the lateral periaqueductal gray (lPAG): Effects on blood pressure and heart rate in basic and hypotensive hemorrhagic rats - Vida Alikhani; Reza Mohebbati; Mohammad Naser Shafei (Iranian Journal of Basic Medical Sciences)
Objective(s): The lateral periaqueductal gray (lPAG) is involved in regulating cardiovascular activity. As glutamate is present in this region, the effect of glutamatergic receptors on cardiovascular functions in basic and hypotensive hemorrhagic (Hem) rats was investigated.Materials and Methods: In both basic and hemorrhagic animals, saline, L-glutamate (L-Glu), and ionotropic receptor antagonists (MK-801 and GYK as NMDA and non-NMDA receptor antagonists, respectively) with and without L-Glu microinjected into the lPAG. The heart rate (HR), mean arterial pressure (MAP), and systolic blood pressure (SBP) were captured, and those changes (Δ) were calculated and analyzed.Results: The results showed that in basic conditions, microinjection of MK-801 and GYK alone did not significantly affect cardiovascular parameters, but L-Glu significantly increased all parameters (P<0.001). However, co-injection of GYK and L-Glu significantly attenuated cardiovascular responses induced by L-Glu (P<0.01), whereas MK-801 did not have effects. In Hem hypotensive condition, injection of MK-801 and GYK alone could not significantly change the cardiovascular responses, while L-Glu alone significantly increased these responses (P<0.001). In this condition, Co-injection of L-Glu with GYK attenuates the pressor effect of L-Glu, but MK-801 did not affect it. Conclusion: Findings suggest an excitatory cardiovascular role of the glutamatergic system of lPAG in normotensive conditions mediated by a non-NMDA receptor. However, in hem hypotensive conditions, the endogenous glutamatergic system of lPAG does not affect hem hypotension, while exogenous glutamate via a non-NMDA receptor could improve cardiovascular responses in this condition.